Regulation of Toll-Like Receptors-Mediated Inflammation by Immunobiotics in Bovine Intestinal Epitheliocytes: Role of Signaling Pathways and Negative Regulators - Villena, Julio; Aso, Hisashi; Kitazawa, Haruki (Frontiers in Immunology, 2014)
Intestinal epithelial cells (IECs) detect bacterial and viral associated-molecular-patterns (MAMPs) via germline-encoded pattern-recognition receptors (PRRs) and are responsible for maintaining immunetolerance to the communities of resident commensal bacteria while being also capable to mount immune responses against pathogens. Toll-like receptors (TLRs) are a major class of PRRs expressed on IECs and immune cells, which are involved in the induction of both tolerance and inflammation. In the last decade, experimental and clinical evidence was generated to support the application of probiotics with immunoregulatory capacities (immunobiotics) for the prevention and treatment of several gastrointestinal inflammatory disorders in which TLRs exert a significant role. The majority of these studies were performed in mouse and human cell lines and, despite the growing interest in the bovine immune system due to the economic importance of cattle as livestock, only few studies have been conducted on cattle. In this regard, our group have established a bovine intestinal epithelial (BIE) cell line originally derived from fetal bovine intestinal epitheliocytes and used this cell line to evaluate the impact of immunobiotics in TLR-mediated inflammation. This review aims to summarize the current knowledge of the beneficial effects of immunobiotics in the regulation of intestinal inflammation/infection in cattle. Especially we discuss the role of TLRs and their negative regulators in both the inflammatory response nd the beneficial effects of immunobiotics in bovine IECs. This review article emphasizes the cellular and molecular interactions of immunobiotics with BIE cells through TLRs and gives the scientific basis for the development of immunomodulatory feed for bovine healthy development.